Neuro-oncology management during the COVID-19 pandemic with a focus on WHO grades III and IV gliomas - Bernhardt, Denise; Wick, Wolfgang; Weiss, Stephanie E; Sahgal, Arjun; Lo, Simon S; Suh, John H; Chang, Eric L; Foote, Matthew; Perry, James; Meyer, Bernhard; Vajkoczy, Peter; Wen, Patrick Y; et al. (Neuro-Oncology, 2020)
Because of the increased risk in cancer patients of developing complications caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), physicians have to balance the competing risks of the negative impact of the pandemic and the primary tumor disease. In this consensus statement, an international group of experts present mitigation strategies and treatment guidance for patients suffering from high grade gliomas (HGGs) during the coronavirus disease 2019 (COVID-19) pandemic.international experts in the treatment of HGG contributed to this consensus-based practice recommendation, including neuro-oncologists, neurosurgeons, radiation oncologists, and a medical physicist. Generally, treatment of neuro-oncological patients cannot be significantly delayed and initiating therapy should not be outweighed by COVID-19. We present detailed interdisciplinary treatment strategies for molecular subgroups in 2 pandemic scenarios, a scale-up phase and a crisis phase.This practice recommendation presents a pragmatic framework and consensus-based mitigation strategies for the treatment of HGG patients during the SARS-CoV-2 pandemic.
Gesehen am 05.02.2021